Secondary metabolites compound of sea plumes gorgonian (Rumphella, Isis and Ellisella) from Maumere Water- East Nusa Tenggara Indonesia. Issue 1 (April 2020) - Teffu, Y H; Kase, A G O; Trianto, A; Wijayanti, D P
Abstract: The abundance and diversity of gorgonian sea plumes in the aquatic of Maumere - East Nusa Tenggara lead us to undertake research of their secondary metabolites. The objective of this study was to identify the species sea plumes gorgonian and to characterize its secondary metabolites that had biological activity. Identification of genus was based on morphology characteristics: sclerite forms; while phytochemical tests was undertaken on gorgonian extract of sea plumes. The phytochemical test showed that secondary metabolites of gorgonian extract contained alkaloids, flavonoids, quinone, steroid/triterpenoid, tannin and saponin. The identification results were found three gorgonian genera, namely Genus Rumphella, Isis and Ellisella . The highest yield of gorgonian extract was Rumphella sp. 7.84%. Components of secondary metabolites identified were alkaloids, flavonoids, quinone, steroids, triterpenoids, tannins/phenolics and saponin.